Esophageal Motility Disorders: Current Concepts of Pathogenesis and Treatment - Peter J Kahrilas (Canadian Journal of Gastroenterology)
Current concepts of esophageal motility disorders are summarized. Primary data sources were located via MEDLINE or cross-citation. No attempt was made to be comprehensive or inclusive of the literature because fewer than 10% of citations are discussed. Instead, emphasis was placed on new developments in diagnosis, therapeutics, and practice patterns. Controlled therapeutic trials and pathophysiological observations are emphasized. Achalasia is a rare disease of failed lower sphincter relaxation and aperistalsis. Diffuse esophageal spasm (DES), an equally rare disease, is defined by non-propagated esophageal contractions. Nonspecific motility disorders, including nutcracker esophagus and hypertensive lower esophageal sphincter, are identified only by manometry and are ten times as prevalent. Neuromuscular pathology is evident only with achalasia (myenteric plexus neurons destruction). Pharmacological therapies have limited efficacy with achalasia; more limited with DES; and none with the nonspecific motility disorders. More efficacious therapies for the nonspecific disorders are directed at associated reflux disease or psychiatric disorders. Pneumatic dilation is effective therapy for achalasia 72% of instances, but frequently requires repeat dilation and is complicated by a 3% perforation rate. Surgical myotomy is effective in 88% of achalasics; morbidity from thoracotomy has been the major limitation but this has been sharply reduced with a laparoscopic approach. In conclusion, although it has been suggested that esophageal motility disorders are distinct clinical entities, critical review of the literature supports this only in the case of achalasia, a disease of well defined pathophysiology, functional disturbance, and therapies. This clarity diminishes progressively for DES and non-specific esophageal motility disorders.